Estilos de crianza como factor de riesgo en la ideación suicida en adolescentes. - Loor Portilla, Angélica María (2024)
The present study had the objective of analyzing parenting styles as a risk factor for suicidal ideation in adolescents. The study is a descriptive bibliographic and documentary study. The population was represented by 473 scientific articles with a quantitative focus on the study variables. Afterward, a non-probabilistic intentional sample was described using a literature revision. Then, the methodological quality was evaluated using the CRF-QS instrument, and 54 articles were selected. The results determined that the most predominant parenting style is authoritarian, followed by negligent and permissive. In addition, another parenting style, authoritative parenting, was used, decreasing the levels of creativity. It was also discovered that there were high levels of suicidal ideation in adolescents due to inadequate parenting. In conclusion, parenting styles are a risk factor for suicidal ideation in adolescents, being this a vulnerable population that, under the influence of insufficient parenting styles, produces adverse effects on psychosocial and integral development.